2017
DOI: 10.1111/cge.12919
|View full text |Cite
|
Sign up to set email alerts
|

Alport syndrome: impact of digenic inheritance in patients management

Abstract: Alport syndrome (ATS) is a genetically heterogeneous nephropathy with considerable phenotypic variability and different transmission patterns, including monogenic (X-linked/autosomal) and digenic inheritance (DI). Here we present a new series of families with DI and we discuss the consequences for genetic counseling and risk assessment. Out of five families harboring variants in more than one COL4 gene detected by next generation sequencing (NGS), minigene-splicing assay allowed us to identify four as true dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 37 publications
4
69
0
3
Order By: Relevance
“…Our findings provide substantial evidence for possible digenic inheritance of Alport syndrome by concomitant mutations also in this combination of Alport genes, as to our knowledge only one single patient has been reported so far with concomitant COL4A3/COL4A5 mutations, that is, a de novo COL4A5 mutation combined with an inherited COL4A3 mutation, which were associated with a notably severe phenotype [15].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our findings provide substantial evidence for possible digenic inheritance of Alport syndrome by concomitant mutations also in this combination of Alport genes, as to our knowledge only one single patient has been reported so far with concomitant COL4A3/COL4A5 mutations, that is, a de novo COL4A5 mutation combined with an inherited COL4A3 mutation, which were associated with a notably severe phenotype [15].…”
Section: Discussionsupporting
confidence: 50%
“…Together, the results indicate that Alport syndrome is under digenic control by COL4A3/COL4A4 and COL4A4/COL4A5. There is only one report on a patient with Alport syndrome with an inherited COL4A3 mutation combined with a de novo COL4A5 mutation [15]. Our study reports the findings of at least 6 more cases on a pedigree with 2 concomitant COL4A3/COL4A5 mutations.…”
Section: Possibility Of Digenic Inheritancesupporting
confidence: 58%
“…Recently, Mencarelli et al [2015] suggested that a digenic inheritance pattern should be considered in AS. The clinical manifestations of digenic mutations in COL4A3 and COL4A4 varied obviously, and the correlation of genotype and phenotype is still not fully known [Schaffer, 2013;Mencarelli et al, 2015;Fallerini et al, 2017]. In our report, heterozygous COL4A3 and COL4A4 mutations in cis were detected in the patients II-2, III-4, III-9, and IV-2 who showed isolated hematuria and normal renal function without other extrarenal manifestations ( Table 1 ).…”
Section: Discussionmentioning
confidence: 53%
“…All these results showed that COL4A3 and COL4A4 digenic mutations in cis are responsible for BFH. However, Fallerini et al [2017] reported 2 families having COL4A3 and COL4A4 mutations in cis with a more severe phenotype. The phenotype of a gene dosage effect and synergism in COL4A3 / COL4A4 genes is not fully elucidated, and therefore expanding the BFH family sample sizes is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation